INSTAGRAM SEBAGAI MEDIA PEMBENTUK PERSONAL BRANDING - Haryadi Mujianto; Zikri Fachrul Nurhadi; Kenny Kharismawati (Prodi Ilmu Komunikasi Universitas Putera Batam, 2021)
This study discusses Instagram as a personal branding media. The purpose of this research is to describe the factors that established personal branding. The research method used in this research is descriptive qualitative research. The informants in this study consisted of 3 celebgrams at the Garut City, Informants are determined by purposive sampling. The results of this study are, branding on Instagram social media is an effort to present information, messages and impressions through the activities carried out. Personal branding that is formed based on the main dimensions of the formation of personal branding that they show on each Instagram account including style, caption, special abilities or competences in a certain area controlled by celebrities and self-standards can form personal branding through a polish and well communication method.